Safety and Risk of Major Complications With Diagnostic Cardiac Catheterization. (July 2019) - Al-Hijji, Mohammed A.; Lennon, Ryan J.; Gulati, Rajiv; El Sabbagh, Abdallah; Park, Jae Yoon; Crusan, Daniel; Kanwar, Amrit; Behfar, Atta; Lerman, Amir; Holmes, David R.; Bell, Malcolm; Singh, Mandeep
Abstract : Background: We aim to study the incidence of major complications related to procedure defined as in-hospital death, myocardial infarction, stroke, pericardial effusion or tamponade, percutaneous coronary intervention due to iatrogenic coronary dissection, or unplanned bypass surgery within 72 hours after diagnostic left heart catheterization (LHC; primary end point). Furthermore, all causes of in-hospital death after LHC were adjudicated and reported (secondary end point). Methods and Results: Diagnostic LHC procedures (aortic angiography; coronary, including graft, angiography; and left ventricular angiography) from January 1, 2002, through December 31, 2013, were identified using the clinical scheduling system at Mayo Clinic, Rochester, and complications were identified through electronic records. International Classification of Diseases, Ninth Revision billing codes were used. Registration was queried to identify all-cause mortality. All events were reviewed and adjudicated. There were 43 786 diagnostic LHC procedures; 97.3% were coronary angiograms. The mean age of patients was 64.5 years (13.6), and the majority were male (61.5%). Primary end point was seen in 36 (0.082%) procedures or 8.2 of 10 000 LHCs. Combined right sided procedures with LHC did not increase the risk of major complications. Cardiogenic and septic shock, cardiac arrhythmia, and postsurgical complication were the most common causes of in-hospital death after LHC. Conclusions: The overall rates of major complications related to diagnostic cardiac catheterization procedures are extremely rare. The majority of the deaths occurring post-diagnostic LHC procedures were secondary to acute illness rather than directly related to diagnostic procedure. Abstract : Supplemental Digital Content is available in the text.